2012
DOI: 10.1002/sia.5122
|View full text |Cite
|
Sign up to set email alerts
|

Dual beam depth profiling of polymer materials: comparison of C60 and Ar cluster ion beams for sputtering

Abstract: Dual beam depth profiling was applied in order to investigate the possibilities and limitations of C 60 and Ar cluster ion sputtering for depth profiling of polymer materials. Stability and intensity of characteristic high mass molecular ion signals as well as sputter yields will be compared. For this purpose, different beam energies resulting in 2-10 eV/atom for Ar n and 167-667 eV/atom for C 60 sputtering were applied to various polymer samples. From our experiments, we can conclude that most of the limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 17 publications
10
71
0
Order By: Relevance
“…It has been reported recently that the shape of the impact angle dependence of sputtering yield changes signicantly with the size of the projectile bombarding organic samples and for large projectiles exhibits the shape known from the studies of atomic projectile bombardment [24]. Similar observation has been recently made in experiments with Ar 2000 on polymer samples [5]. It has been proposed that a washing out mechanism is responsible for the observed phenomenon [24].…”
Section: Introductionsupporting
confidence: 70%
“…It has been reported recently that the shape of the impact angle dependence of sputtering yield changes signicantly with the size of the projectile bombarding organic samples and for large projectiles exhibits the shape known from the studies of atomic projectile bombardment [24]. Similar observation has been recently made in experiments with Ar 2000 on polymer samples [5]. It has been proposed that a washing out mechanism is responsible for the observed phenomenon [24].…”
Section: Introductionsupporting
confidence: 70%
“…As the literature stands at present, films as thick as 10 μm have been depth profiled without signal loss for both PMMA and PS. 135 Direct comparisons of the GCIB source with C 60 can be observed in Table 5.1, where it is clearly seen that the best depth resolutions, maximum erosion depths, and sputter rate linearities have indeed been obtained when employing the GCIB source. Further enhancements in sputter properties are observed when employing sample rotation.…”
Section: The Gas Cluster Ion Beam (Gcib)mentioning
confidence: 99%
“…Mochiji et al 44 reported the use of an Ar cluster source with SIMS showing impressive results. Recently, Rading et al 45,46 have described the operation of an Ar cluster source on an ION-TOF ToF-SIMS V instrument, where they have employed an additional mass separation method via a 90 • pulsing system to further enhance mass separation as illustrated in Figure 3.11. They claim that the cluster size distribution can be narrowed such that (n/ n) is approximately 60-100.…”
Section: Jets and Electron Impact (Massive Gas Clusters)mentioning
confidence: 99%